The Influence of Institutional Ownership, Board of Commissioners, and Audit Committee on Company Value with Financial Performance as a Moderator - Saputri, Sitty Nenden (International Journal of Science and Society, 2025)
The purpose of this study is to analyze the effect of institutional ownership, independent commissioners, and audit committees on firm value with financial performance (Return on Equity/ROE) as a moderating variable. This study focuses on financial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period to determine how corporate governance mechanisms and profitability interact to influence firm value. This research employs a quantitative approach using panel data regression analysis. The sample consists of 105 financial sector observed from 2020 to 2024, resulting in 524 unbalanced panel observations. The model estimation applies the Random Effect Model (REM) based on the results of the Lagrange Multiplier (LM) and Hausman tests. The variables analyzed include independent commissioners (JDKI), audit committee (KA), institutional ownership (KI), and financial performance (ROE), with interaction terms (JDKIROE, KAROE, KI*ROE) used to test moderation effects. The empirical results reveal that institutional ownership (KI) has a positive and significant effect on firm value (PBV), indicating that higher institutional ownership improves market perception through better monitoring and governance. Conversely, the audit committee (KA) shows a negative and significant effect on firm value, suggesting that an ineffective audit committee may reduce investor confidence. The independent commissioner (JDKI) and ROE have no significant direct effects on firm value. The moderation test indicates that ROE does not significantly moderate the relationship between JDKI, KI, and firm value, but slightly moderates the relationship between the audit committee and firm value, implying that profitability can weaken the negative effect of audit committees on firm value.